Worm gear’s operating barriers - Tadeusz MARCINIAK; Dariusz OSTROWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The main factor that characterize the durability of worm gears are the materials from which the elements are made. Distinct from toothed gear, in which, in most of cases collaborating elements are made from toughened steel, in worm gears the standard is collaborating of toughened worm and relatively soft worm wheel, made from bronze. Applications of different materials have not given good results. Due to this reason a worm gear operating barriers, which not similar to different types of gears, take place. The article presents the mechanism of worm gears utilization, which in most of cases decide about its durability. Theoretical basis of operating barriers have been given, with particular emphasis on fatigue and abrasive wear barriers, which are most common reason of durability limitation. Operating test results have been presented as well as trials, that were to determine the durability depending on operation conditions. Recommendations have been formulated for proper material selection, operating conditions as well as valuations of gear durability stage.